Determinants of Anemia among Female Adolescents in Maubesi Health Center, North Central Timor District, East Nusa Tenggara - Frederica Rosita Bani; Niken Meilani; Munica Rita Hernayanti (JURNAL INFO KESEHATAN, 2025)
Anemia in Indonesia remains a significant public health concern, especially among adolescents. Several diverse factors contribute to anemia in this age group, including suboptimal nutritional intake habits. This study aimed to determine the factors associated with anemia among female adolescents in Lanaus Village, Maubesi District. This was a cross-sectional study conducted in April 2023. The population consisted of all female adolescents in Lanaus Village, totaling 171 individuals. The sample size was calculated using Slovin’s formula, resulting in 63 respondents. Purposive random sampling was used as the sampling technique, and participants were selected based on predefined inclusion and exclusion criteria. The research instrument was a structured questionnaire. Data analysis included univariate analysis, chi-square tests, and logistic regression. The study found a significant association between anemia and the following factors: compliance with iron supplementation (p-value = 0.002), socioeconomic status (p-value = 0.008), and breakfast habits (p-value = 0.000). On the other hand, there was no significant relationship between BMI and anemia (p-value = 0.096). Among the significant factors, compliance with iron supplementation and breakfast habits was most strongly associated with anemia. Breakfast habits were identified as the dominant factor influencing anemia among female adolescents in Lanaus Village, with a p-value of 0.019 and an odds ratio (OR) of 15.427. Adolescents who did not regularly eat breakfast were found to be 15.42 times more likely to experience anemia. It is essential for adolescents to understand the importance of regular breakfast consumption and adherence to iron supplementation as key strategies in the prevention and control of anemia.